Pengaruh Konflik Dan Stres Kerja Terhadap Kepuasan Kerja Dengan Lingkungan Kerja Sebagai Variabel Intervening Pada PT. Usaha Sawit Mandiri (USM) Jorong Simpang Kec. Koto Balingka Kab. Pasaman Barat - Amelya Fitri; Ramdani Bayu Putra; Nila Pratiwi; Hasmaynelis Fitri (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This research aims to analyze how much influence work conflict and stress has on job satisfaction with the work environment as an intervening variable at PT. Mandiri Palm Oil Business (USM) Jorong Simpang Kec. Koto Balingka District. West Pasaman. The data collection method is through surveys and distributing questionnaires, with a sample of 89 respondents. The analysis method used is path analysis using the SmartPls application. Based on the research results, it shows that there is a positive and significant influence between conflict on the work environment. There is a positive and significant influence between Job Stress on the Work environment. There is a positive and significant influence between Conflict and Job Satisfaction. There is a negative and insignificant influence between Job Stress and Job Satisfaction. . There is a positive and significant influence between the Work Environment and Job Satisfaction. There is a positive and significant influence between Conflict on Job Satisfaction and the Work Environment as an intervening variable. There is a positive and significant influence between Job Stress on Job Satisfaction with the Work Environment as an intervening variable.